2006
DOI: 10.2105/ajph.2005.064840
|View full text |Cite
|
Sign up to set email alerts
|

Couples’ Immigration Status and Ethnicity as Determinants of Breastfeeding

Abstract: The Hispanic paradox may extend to other non-Hispanic immigrants for breastfeeding behaviors, but may not be true for Hispanic mothers born in the United States. Low rates of breastfeeding for Hispanic American mothers indicate that they should not be overlooked by breastfeeding promotion programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
143
2
5

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 134 publications
(161 citation statements)
references
References 34 publications
11
143
2
5
Order By: Relevance
“…This finding has also been previously reported in multicultural societies, with each additional year of the US residency found responsible for a decrease in the odds of breastfeeding by 4% (28). Moreover, the ethnic-nativity differentials in breastfeeding duration in the study of Singh et al were even greater than those observed for breastfeeding initiation (19).…”
Section: Table 3 Adjusted Odds Ratios (Or) and 95% Confidence Intervsupporting
confidence: 83%
“…This finding has also been previously reported in multicultural societies, with each additional year of the US residency found responsible for a decrease in the odds of breastfeeding by 4% (28). Moreover, the ethnic-nativity differentials in breastfeeding duration in the study of Singh et al were even greater than those observed for breastfeeding initiation (19).…”
Section: Table 3 Adjusted Odds Ratios (Or) and 95% Confidence Intervsupporting
confidence: 83%
“…Keegan et al, 34 further noted that this pattern is consistent with the corresponding differences in breast cancer incidence rates in the state. Our results are consistent with published reports on breastfeeding, which show that women born outside the US are more likely to breastfeed than those who are born in the US [36][37][38][39][40][41] and that language acculturation also plays a role in whether women choose to breastfeed, particularly among MAs. Results of studies that considered SES variables in their models show that less-acculturated women are more likely to breastfeed than those who are more acculturated.…”
Section: Discussionsupporting
confidence: 92%
“…Results of studies that considered SES variables in their models show that less-acculturated women are more likely to breastfeed than those who are more acculturated. 39,[42][43][44] Our findings show a substantially lower prevalence and duration of breastfeeding in MA women versus women residing in Mexico, and we also observed a gradient of decreasing breastfeeding with increasing language acculturation in MA women. Our results are also largely in agreement with those of John et al, who assessed migration history, acculturation, and breast cancer risk among Hispanic women (predominantly of Mexican descent).…”
Section: Discussionmentioning
confidence: 69%
“…Our analyses nevertheless clearly show the importance of parent health 6 48,49 and duration of residence in the United States. 50 Finally, our study population, which was largely publicly insured, may not be representative of broader populations.…”
Section: Discussionmentioning
confidence: 99%